2001
DOI: 10.1086/320222
|View full text |Cite
|
Sign up to set email alerts
|

First Results from the X‐Ray and Optical Survey of theChandraDeep Field South

Abstract: We present our Ðrst results from 120 ks of X-ray observations obtained with the Advanced CCD Imaging Spectrometer on the Chandra X-Ray Observatory. The Ðeld of the two combined exposures is 0.096 deg2 and the detection limit is to a S/N of 2 (corresponding to D7 net counts). We reach a Ñux of 2 ] 10~16 erg s~1 cm~2 in the 0.5È2 keV soft band and 2 ] 10~15 erg s~1 cm~2 in the 2È10 keV hard band. Our combined sample has 144 soft sources and 91 hard sources, for a total of 159 sources. Fifteen sources are detecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
558
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 470 publications
(606 citation statements)
references
References 36 publications
45
558
3
Order By: Relevance
“…The average hardening of faint sources agrees with the shape of the CXB in approximately the same energy range (Marshall et al 1980), as already found at lower energies (e.g., Mushotzky et al 2000;Brandt et al 2001;Giacconi et al 2001). There is one notable outlier with a negative Γ valuethe CT thick source in the COSMOS field reported by C15 (cosmos330 in Table 2).…”
Section: Nustar Spectral Analysissupporting
confidence: 83%
“…The average hardening of faint sources agrees with the shape of the CXB in approximately the same energy range (Marshall et al 1980), as already found at lower energies (e.g., Mushotzky et al 2000;Brandt et al 2001;Giacconi et al 2001). There is one notable outlier with a negative Γ valuethe CT thick source in the COSMOS field reported by C15 (cosmos330 in Table 2).…”
Section: Nustar Spectral Analysissupporting
confidence: 83%
“…The CXB is the superposition of resolved and unresolved emission coming from distant X-ray sources, such as AGNs (Giacconi et al 2001). Although this component is generated by sources with different redshift and spectral distributions, it can be modelled by a power law with a photon index Γ = 1.42 (e.g., Lumb et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…the sensitivity of the deepest surveys performed by the Chandra observatory (i.e. the Chandra deep field North and South, Bauer et al 2004;Giacconi et al 2001), the larger collecting area of XMM-Newton offers the possibility to perform a spectral analysis of a large fraction of the detected sources down to the confusion limit, opening up a powerful window into the cosmological evolution of the X-ray universe.…”
Section: Introductionmentioning
confidence: 99%